Inkjet-printed graphene Hall mobility measurements and low-frequency noise characterization. Issue 12 (18th March 2020) - Calabrese, Gabriele; Pimpolari, Lorenzo; Conti, Silvia; Mavier, Fabrice; Majee, Subimal; Worsley, Robyn; Wang, Zihao; Pieri, Francesco; Basso, Giovanni; Pennelli, Giovanni; Parvez, Khaled; Brooks, David; et al.
Abstract : Inkjet printed graphene is in-depth investigated by means of Hall mobility measurements, low-temperature magnetoresistance analysis, and low frequency noise characterization. Abstract : We report room temperature Hall mobility measurements, low temperature magnetoresistance analysis and low-frequency noise characterization of inkjet-printed graphene films on fused quartz and SiO2 /Si substrates. We found that thermal annealing in vacuum at 450 °C is a necessary step in order to stabilize the Hall voltage across the devices, allowing their electrical characterization. The printed films present a minimum sheet resistance of 23.3 Ω sq −1 after annealing, and are n-type doped, with carrier concentrations in the low 10 20 cm −3 range. The charge carrier mobility is found to increase with increasing film thickness, reaching a maximum value of 33 cm 2 V −1 s −1 for a 480 nm-thick film printed on SiO2 /Si. Low-frequency noise characterization shows a 1/ f noise behavior and a Hooge parameter in the range of 0.1–1. These results represent the first in-depth electrical and noise characterization of transport in inkjet-printed graphene films, able to provide physical insights on the mechanisms at play.